Seasonal changes in potential net photosynthesis of sun and shade leaves of Fagus sylvatica L. - Jayasekera, R.; Schleser, G.H. (Elsevier, 1988)
Sun and shade leaves of the deciduous tree, Fagus sylvatica, were investigated for their potential photosynthetic activity during the course of one growing season. During the initial period of leaf development and expansion, sun leaves exhibited relatively higher photosynthetic rates. After full expansion of leaves, shade leaves had a higher activity in potential net photosynthesis until about the end of August. Low diffusion resistance for CO2/O2 and higher activities of photosystems in shade leaves seem to be the main causes of their higher photosynthetic potential.
Keywords: Beech; Fagus sylvatica L.; potential net photosynthesis; seasonal changes